Simulation and optimisation of a piezo-compressor - Wei, Xiaojin. (2008)
A new compressor is proposed based on an idea of replacing the conventional electric motor and the crank mechanisms in a reciprocating compressor with a piezo-actuator. This new compressor is called piezo-compressor. It has a simpler structure and fewer moving parts as compared with the conventional reciprocating compressor. The piston of the compressor moves with reciprocating action but the compressor is free from the crank mechanisms and thus it is expected to have less friction loss.